2010
DOI: 10.1021/ma101218q
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Adsorption by δ and ε Crystalline Phases of Syndiotactic Polystyrene Aerogels

Abstract: The H2 uptake from s-PS samples exhibiting different crystalline phases and different morphologies has been studied by gravimetric measurements at 77 K in the hydrogen pressure range from 0 up to 1.7 MPa and compared with molecular simulations relative to s-PS crystals. Gravimetric experiments show that the molecular hydrogen sorption is strongly dependent on the sample morphology and is maximum for low-density polymer aerogels. However, independently of the morphology, the H2 uptake is minimum for the dense β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 49 publications
3
45
0
Order By: Relevance
“…The unit cell of nanoporous δ (δ e ) contains eight styrene monomeric units along with two identical cavities with density 0.98 g/cm 3 , whereas the density of the amorphous phase is 1.05 g/cm 3 [14,42]. These nanoporous crystalline forms were found to have the capability to absorb molecules like CO 2 and H 2 [44,45] as well as organic molecules [16,46]. Hence, these materials can be used as sensors, [47][48][49][50] molecular sieves, [46,[51][52][53], catalysts [54], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The unit cell of nanoporous δ (δ e ) contains eight styrene monomeric units along with two identical cavities with density 0.98 g/cm 3 , whereas the density of the amorphous phase is 1.05 g/cm 3 [14,42]. These nanoporous crystalline forms were found to have the capability to absorb molecules like CO 2 and H 2 [44,45] as well as organic molecules [16,46]. Hence, these materials can be used as sensors, [47][48][49][50] molecular sieves, [46,[51][52][53], catalysts [54], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The thermoplastic nature of these materials allows an easy processing to products suitable for several applications, like films, membranes, and foams, as well as their recycling. As a consequence, a number of applications in the field of chemical separations, molecular sensorics, and catalysis for these inexpensive and reusable materials have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…For syndiotactic polystyrene it has been shown that the sorption kinetics but also the uptake values for molecules presenting a poor solubility in the polymer amorphous phase depend on the sample morphology. In particular it has been observed that both kinetics and uptake values can be greatly increased by using aerogels instead of powder or film samples.…”
Section: Resultsmentioning
confidence: 99%